Large degree vertices in longest cycles of graphs, II - Binlong Li; Liming Xiong; Jun Yin (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2019)
In this paper, we consider the least integer d such that every k-connected graph G of order n (and of independent number α) has a longest cycle containing all vertices of degree at least d. We completely determine the d when k = 2. We propose a conjecture for those k-connected graph, where k ≥ 3.